PENGARUH SUPERVISI AKADEMIK DAN GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DENGAN KEPUASAN KERJA DI RAUDHATUL ATHFAL KEC CIBEBER KOTA CILEGON - Mahdi, Ahmad; B. Herawan Hayadi; Furtasan Ali Yusuf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research examines the influence of leadership style, job satisfaction, and academic supervision on teacher performance at the Raudhatul Athfal School, Cibeber District, Cilegon City. Some of the problems faced regarding teacher performance include the teacher's inability to prepare lessons, manage the class well, and use varied learning strategies, which leads to boring learning for students. The purpose of this research is to determine and test the influence of: (1) leadership style on teacher job satisfaction, (2) leadership style on teacher performance, (3) job satisfaction on teacher performance, (4) academic supervision on teacher job satisfaction, and (5) academic supervision of teacher performance. This research uses quantitative methods with a correlational approach, and data is collected through questionnaires. Data analysis was carried out using SmartPLS 3.2 and structural equation modeling (SEM) techniques. The results of the research show that: (1) leadership style has a positive effect on teacher job satisfaction, (2) leadership style has a positive effect on teacher performance, (3) job satisfaction has a positive effect on teacher performance, (4) academic supervision does not have a positive effect on satisfaction teacher work, and (5) academic supervision has a positive effect on teacher performance. The implications of this research indicate that improving leadership styles and effective academic supervision can contribute to improving teacher performance, although academic supervision does not directly affect job satisfaction.